Development of RFID-based temperature and attendance monitoring system - Muhammad Shafiq Isyraf, Nordin (2022)
Nowadays, in a new norm of COVID-19, teacher on duty needs to take a student's daily temperature for every morning of school days and record the data in the logbook. The student or teacher must touch the object such as book and pen to write the data. This will increase risk for COVID-19 to spread around there. To overcome this problem, RFID is the most suitable technology to replace the existing procedure. This project is an automated system that can automatically read and record the student's temperature and most importantly is touch less device. Furthermore, by using Arduino as core to combine multiple components such as OLED screen, temperature sensor, and Bluetooth for communication in circuit. The database is more manageable and more secure because created by using software PLX-DAQ with Excel. Thus, will make the devices more versatile, portable and easy to uses by any user.